Evaluation of Cuban institutional repositories - Gutiérrez Sosa, Denia (2024)
The evaluation of repositories has been studied from different perspectives due to its importance in checking whether they really fulfill the purpose for which they were created. The objective of this research is to evaluate the digital repositories of science and technology existing in Cuba based on the application of the Guide for the Evaluation of Institutional Research Repositories published by the Spanish Foundation for Science and Technology. Quantitative research of a descriptive nature is presented that is supported by data collection and documentary analysis. The repository websites are consulted as the main means of verifying the criteria to be evaluated. The results obtained from the analysis of indicators related to visibility, policies, legal aspects, metadata, metadata interoperability and access to content, logs and statistics, services and functionalities made it possible to diagnose the evaluated repositories and identify guidelines to, address the creation of an Open Access infrastructure that allows harmonizing the collection, storage, organization, access, dissemination and use of national scientific and technological production treated in a decentralized manner from institutional and/or thematic repositories and the integration of their resources, goods and services in the National Digital Library of Science and Technology.